The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1021/acs.jmedchem.1c02140
|View full text |Cite
|
Sign up to set email alerts
|

Novel β-Hairpin Antimicrobial Peptides Containing the β-Turn Sequence of -RRRF- Having High Cell Selectivity and Low Incidence of Drug Resistance

Abstract: The emergence of multidrug-resistant bacteria has dramatically increased the lethality, level of resistance, and difficulty of treatment. In this study, a series of new antimicrobial peptides (AMPs) based on the β-hairpin structure with the template (XY) 2 RRRF(YX) 2 -NH 2 (X: hydrophobic amino acids; Y: cationic amino acids) were synthesized; surprisingly, almost all of the new peptides have strong antibacterial activity and negligible hemolytic toxicity. Particularly, the therapeutic index (TI) values of F(R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 61 publications
2
32
0
Order By: Relevance
“…Also, the more hydrophobic peptides induced higher PI fluorescence intensity than the less hydrophobic peptides (AS4-1 < AS4-5 < AS4-9) (Figure D). The AMP-induced bacterial membrane permeabilization generally results in continuous fluorescent dye transmembrane translocation for a long time even after bacterial cell death. , In the present study, although AS4-1, AS4-5, and AS4-9 needed less than 120 min to kill the bacterial cells in killing kinetics assay (Figure A), we can find that the calcein and PI fluorescence intensity induced by them continuously increased with the time extension to 180 min. All the results above prove that hydrophobicity, rather than net charge, is the key structural parameter for α-helical AMPs to permeabilize the bacterial IM and lead to the subsequent cell lysis.…”
Section: Resultssupporting
confidence: 49%
“…Also, the more hydrophobic peptides induced higher PI fluorescence intensity than the less hydrophobic peptides (AS4-1 < AS4-5 < AS4-9) (Figure D). The AMP-induced bacterial membrane permeabilization generally results in continuous fluorescent dye transmembrane translocation for a long time even after bacterial cell death. , In the present study, although AS4-1, AS4-5, and AS4-9 needed less than 120 min to kill the bacterial cells in killing kinetics assay (Figure A), we can find that the calcein and PI fluorescence intensity induced by them continuously increased with the time extension to 180 min. All the results above prove that hydrophobicity, rather than net charge, is the key structural parameter for α-helical AMPs to permeabilize the bacterial IM and lead to the subsequent cell lysis.…”
Section: Resultssupporting
confidence: 49%
“…The results demonstrated that GHb3K and GHbK4R not only have good antibacterial activity in vitro but also show better therapeutic efficacy than vancomycin in acute pneumonia in vivo. It was reported that F­(RI)­2R and F­(KW)­2K exhibited anti-infection effects in a mouse model of pulmonary infections by S. aureus . Although F­(RI)­2R and F­(KW)­2K showed remarkable efficacy in vivo, they were toxic to the lung and liver.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that F(RI)2R and F(KW)2K exhibited anti-infection effects in a mouse model of pulmonary infections by S. aureus. 44 Although F(RI)2R and F(KW)2K showed remarkable efficacy in vivo, they were toxic to the lung and liver. In comparison, GHb3K and GHbK4R exhibited superior bactericidal properties, low toxicity, and high stability.…”
Section: Acs Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane disruptive antimicrobial peptides (AMPs), which occur naturally as part of the innate immune system, offer an opportunity to address multidrug-resistant (MDR) bacteria because of their unspecific mechanism of action, against which resistance does not occur easily. Such AMPs are however unstable in serum and most often toxic owing to their membrane disruptive amphiphilic and usually α-helical structure triggering their antibacterial effect. Their properties can be improved by sequence optimization, whereby the most versatile approach consists in introducing non-natural structural elements such as d -amino acids, non-natural residues, β- or γ-amino acids, , isopeptide bonds, or entirely non-peptidic elements such as spermine or fatty acids. , A complete redesign of AMPs is also possible in the form of dimers, cyclic or bicyclic staples, small molecules, peptoids, , foldamers, or dendrimers. , …”
Section: Introductionmentioning
confidence: 99%